Effects of titanium dioxide additions on flash ignition characteristics of aluminum and iron nanoparticles - Yu, Runtian; Liu, Yanxiong; Liu, Guannan; Ying, Yaoyao; Li, Tianjiao; Liu, Dong (Frontiers in Energy Research, 2023)
The flash ignition as a new ignition method has attracted lots of interest. The flash ignition can successfully achieve distributed ignition in a short time. To study the flash ignition and combustion characteristics of titanium dioxide mixed with iron nanoparticles and aluminum nanoparticles, an appropriate amount of titanium dioxide was added to the iron nanoparticles and aluminum nanoparticles to form the composite material. The ignition phenomenon of mixture materials was recorded by the high-speed camera and the temperature distribution of ignited materials was calculated by using the two-color method. The minimum ignition energy of mixture materials with different content of titanium dioxide and total mass was measured to analyze the method to decrease the minimum ignition energy. The results showed that the effect of the added titanium dioxide was insignificant on the combustion phenomenon of the iron nanoparticles. The temperature was still maintained at approximately 850K compared with the pure iron nanoparticles. The minimum ignition energy of the mixture materials increased with the increasing content of titanium dioxide. As for the aluminum nanoparticles, titanium dioxide can enhance the explosion phenomenon occurring at the beginning of the flash ignition. In the exposure process. With the content of titanium dioxide in the range of 0–20%, the minimum ignition energy of the mixture materials decreased greatly. The content increased to the range of 20–40%, the minimum ignition energy was neglected. When the content was further increased to higher than 60%, the minimum ignition energy gradually increased until it gets the saturation condition.